2005
DOI: 10.1007/s00122-005-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenotypic and molecular distances to predict heterosis and F1 performance in Ethiopian mustard (Brassica carinata A. Braun)

Abstract: Predicting heterosis and F1 performance from the parental generation could largely enhance the efficiency of breeding hybrid or synthetic cultivars. This study was undertaken to determine the relationship between parental distances estimated from phenotypic traits or molecular markers with heterosis, F1 performance and general combining ability (GCA) in Ethiopian mustard (Brassica carinata). Nine inbred lines representing seven different geographic regions of Ethiopia were crossed in half-diallel. The nine par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 22 publications
1
39
0
2
Order By: Relevance
“…On the other hand, studies with hybridization performances conducted in mustard and alfalfa showed significant correlation between heterosis and morphological distances; whereas genetic distances calculated on the basis of DNA polymorphism (SSR, RAPD, AFLP markers) did not demonstrate such correlation (Riday et al, 2003;Teklewold and Becker, 2006). No reliable correlation was found using genetic distances by SSR markers to predict specific combining ability of sunflower parental lines (Gvodzenovic et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, studies with hybridization performances conducted in mustard and alfalfa showed significant correlation between heterosis and morphological distances; whereas genetic distances calculated on the basis of DNA polymorphism (SSR, RAPD, AFLP markers) did not demonstrate such correlation (Riday et al, 2003;Teklewold and Becker, 2006). No reliable correlation was found using genetic distances by SSR markers to predict specific combining ability of sunflower parental lines (Gvodzenovic et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…However, the results of different studies are often controversial with respect to connection between genetic distances and heterosis (Riday et al, 2003;Geleta et al, 2004;Teklewold and Becker, 2006;Zeid et al, 2003;Ghaly and Al-Sowayan, 2014;Malini and Vasanthanayaki, 2014;SenthilSingh and Manikandan, 2014). In the present research the level of heterosis of F 1 hybrids, genetic diversity of parental lines based on SSR markers, as well as its connection with specific combining ability of sunflower were studied.…”
Section: Introductionmentioning
confidence: 93%
“…Nevertheless, further comparisons on quantitative traits are needed to select relevant populations. One reason is that genetic distances calculated from neutral markers is only a weak predictor of heterosis in hybrid populations (Cheres et al 2000;Teklewod and Becker 2006). The availability of both COI sequences and microsatellites may also be helpful to monitor the post-release evolution of P. lounsburyi in the field and document genetic events such as drift, admixture and introgression.…”
Section: Discussionmentioning
confidence: 98%
“…However, studies conducted in plants showed inconsistent results. For example, genetic distance was not correlated with heterosis for rice hybrid seed yield (Teklewold and Becker, 2006) and was negatively correlated with heterosis of yield (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 95%